2019
DOI: 10.1620/tjem.247.197
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers’ Perspectives for the Effect of Social Support on their Care Burden and Quality of Life: A Mixed-Method Study in Rural and Sub-Urban Central Japan

Abstract: Japan has adopted community-based integrated long-term care, which has shifted the burden of care from institutions to the home. However, family caregivers have received less attention compared with care recipients. Many family caregivers are also older adults, and it is important that caregivers receive appropriate support to alleviate the burden of care. In rural and suburban area with limited resources compared to urban area, it is necessary to know which support to be prioritized. Therefore, this study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
2
15
0
4
Order By: Relevance
“…This finding is also supported by the literature [15,32,42]. Social support is the strongest positive predictor of health promotion and has a positive effect on caregivers' quality of life [43]. In Greece, social support is greater than in some other countries [44], because of the strong ties that exist between members even of the extended family [45].…”
Section: Discussionsupporting
confidence: 69%
“…This finding is also supported by the literature [15,32,42]. Social support is the strongest positive predictor of health promotion and has a positive effect on caregivers' quality of life [43]. In Greece, social support is greater than in some other countries [44], because of the strong ties that exist between members even of the extended family [45].…”
Section: Discussionsupporting
confidence: 69%
“…Studies have shown that the reliance on females for caregiving were influenced by traditional culture, systems of patriarchy, and strict division of gender roles, where women stay at home and are assigned domestic roles 43 . Similarly, in Japan, the role of caregiving of elders typically falls onto females, either the spouse or an adult child, within the family 44 . Furthermore, caregivers of AD/dementia patients tended to be older than other caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers in families with greater conflict and less adaptability report more depression; besides, the prevalence of depression in caregivers is higher than that in noncaregivers (Vitaliano, Ustundag, & Borson, 2016). Social support is negatively associated with psychological morbidity, burden, and psychological suffering (Haya, Ichikawa, Wakabayashi, & Takemura, 2019;Pagnini et al, 2010). Help and support that caregivers get from family and society can influence perceived burden and caregivers are at high risk of burden when the social support network is scarce (Blanco et al, 2019).…”
mentioning
confidence: 99%